2017
DOI: 10.1111/ijlh.12762
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F mutation can be reliably detected in serum using droplet digital PCR

Abstract: In our study, JAK2 V617F mutation load as low as 1% was reliably detected in serum using ddPCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Our results showed that not only could the JAK2 V617F mutation could be detected in serum by qPCR, but this specimen also presented a mean bias of 4.058% when compared to the paired peripheral blood sample. These results corroborate with the previous description using ddPCR [12], suggesting that the use of serum DNA may allow for increased mutant detection rates. Other serum advantages are: 1) It has less inhibitors than whole blood; 2) it can be directly used in qPCR [14]; and 3) it is more friendly most automated DNA extractions and additional purifications steps are not required to achieve amplifiable DNA [15], allowing increased high-throughput analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that not only could the JAK2 V617F mutation could be detected in serum by qPCR, but this specimen also presented a mean bias of 4.058% when compared to the paired peripheral blood sample. These results corroborate with the previous description using ddPCR [12], suggesting that the use of serum DNA may allow for increased mutant detection rates. Other serum advantages are: 1) It has less inhibitors than whole blood; 2) it can be directly used in qPCR [14]; and 3) it is more friendly most automated DNA extractions and additional purifications steps are not required to achieve amplifiable DNA [15], allowing increased high-throughput analysis.…”
Section: Discussionsupporting
confidence: 92%
“…The authors also found a higher mutant allele burden in serum compared to paired peripheral blood samples, which may allow for increased mutant detection rates for serum. Reliable results were observed when more than 5 ng of serum DNA input was used in the ddPCR [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ddPCR allows assessment of the total copy number of target molecules without the need for standard curves, thus facilitating standardization of quantitation. Despite ddPCR being an error-prone method that needs to be standardized, it is less sensitive to PCR inhibitors and therefore more robust than qPCR [28,29]. In addition, ddPCR proved to be an appropriate technique for the detection of mutations present at low allele frequencies because partitioning of the sample reduces wild-type background signals and therefore enhances accuracy of detection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published detection techniques included; allele-speci c PCR which is sensitive enough to detect 2.5% and another study has 0.01% of sensitivity for mutant DNA (30)(31)(32), droplet digital PCR have sensitivity limit of 96% (33), allele-speci c competitive blocker PCR (ACB-PCR) have 1% (34), an ARMS (35), pyro-sequencing have 5-10%(6, 36), sequencing 10-40% (2,4,15), restriction fragment length polymorphism (RFLP) has 5% (32), high resolution melting curve analysis (HRM) having sensitivity of 0.5-1% (37). Although these approaches are enough sensitive but are not quantitative.…”
Section: Discussionmentioning
confidence: 99%